2022
DOI: 10.3390/biom12070933
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Based Compounds in Antiviral Therapy

Abstract: In recent years, the study of metal complexes and metal-based nanomaterials has aroused particular interest, leading to the promotion of new effective systems for the abatement of various viral diseases. Starting from the analysis of chemical properties, this review focuses on the employment of metal-based nanoparticles as antiviral drugs and how this interaction leads to a substantial enhancement in antiviral activity. The use of metal-based antiviral drugs has also spread for the formulation of antiviral vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The recently solved 3D structures of SARS-CoV-2 M pro in complex with zinc ion [ 16 , 17 , 18 ] showed that the metal ion is bound to the catalytically relevant Cys145 and His 41 residues. Furthermore, a few recent works demonstrated that other metal ions or metal-based compounds, such as rhenium, gold and copper compounds, can be efficient inhibitors of viral proteases [ 19 , 20 , 21 ]. For instance, Auranofin is a representative gold drug that was claimed to exhibit remarkable antiviral properties; notably, the efficacy of Auranofin and some related gold compounds against Papain-like protease was nicely documented by Ingo Ott et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recently solved 3D structures of SARS-CoV-2 M pro in complex with zinc ion [ 16 , 17 , 18 ] showed that the metal ion is bound to the catalytically relevant Cys145 and His 41 residues. Furthermore, a few recent works demonstrated that other metal ions or metal-based compounds, such as rhenium, gold and copper compounds, can be efficient inhibitors of viral proteases [ 19 , 20 , 21 ]. For instance, Auranofin is a representative gold drug that was claimed to exhibit remarkable antiviral properties; notably, the efficacy of Auranofin and some related gold compounds against Papain-like protease was nicely documented by Ingo Ott et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two years, the COVID-19 pandemic caused by the SARS-CoV-2 outbreak resulted in more than 50 million official cases and countless deaths. Due to this, many researchers focused on searching for alternatives to diagnose and treat this virus and others, such as influenza A (H1N1 and H5N1), HIV, Chikungunya, Zika, and Hepatitis C and B [ 55 ].…”
Section: Antimicrobial Activities Of Compounds From Toads’ Cutaneous ...mentioning
confidence: 99%
“…Metallic nanoparticles have gained the interest of researchers due to their unique properties, including small size and high specific surface areas that can help interact with microorganisms, such as bacteria and viruses (Birkett et al, 2022). Otherwise, nanoparticles can enhance cytokine production and induce a hormonal immune response and have the capacity for cell recruitment, biocompatibility, low toxicity, good biodistribution properties, and chemical inertness (Dykman, 2020;Behzadi et al, 2021;Abate et al, 2022). Several metals and metal oxide nanoparticles, including copper, silver, gold, zinc, and titanium, have been studied as antiviral agents.…”
Section: Metals As Virucidesmentioning
confidence: 99%